Passively Q-switched Er, Yb:GdAl3(BO3)4 laser with single-walled carbon nanotube based saturable absorber. (6th February 2017) - Gorbachenya, K N; Kisel, V E; Yasukevich, A S; Prudnikova, M B; Maltsev, V V; Leonyuk, N I; Choi, S Y; Rotermund, F; Kuleshov, N V
Abstract: We demonstrate a passively Q-switched Er, Yb:GdAl3 (BO3 )4 diode-pumped laser emitting near 1.5 µ m. By using a single-walled carbon nanotube (SWCNT) as a saturable absorber, Q-switched laser pulses with energy of 0.8 µ J and duration of 130 ns at a maximum repetition rate of 500 kHz were obtained at 1550 nm.